Flood preparedness, response and recovery of flood affected business owners in shah alam in 2021 - Hwang, Ming Yuan (2022)
In the mid of December 2021, the central of peninsular Malaysia, especially the Shah Alam district, experienced the worst flooding disaster that caused local business owners to bear billions of Ringgit losses. They face critical challenges in the flood recovery process during the post-Covid-19 pandemic recovery. As such, this research study aims to investigate the correlation between flood impact and flood preparedness, response and recovery of Shah Alam’s business owners, investigate the factors that influence flood damage and provide recommendations to mitigate floods for the business owners in Shah Alam. Quantitative research design has been selected as the research instrument of this study, while online and on-field data collecting survey methods via Google Forms are adapted. The questionnaire consists of 3 sections with a total of 24 guided response type questions to collect useful information from the targeted population, business owners affected by Shah Alam Flood 2021. In the end, a total of 122 responses were collected, but only 120 responses are qualified to be used in the following SPSS software-based analysis. The findings reached in this study show that flood preparedness has the highest negative influence on the flood impact on the business owners, followed by the flood response of business owners. However, flood recovery is statistically proven to have a moderate positive relationship with flood impact among the three independent variables. This study further determines 2 ordinal type factors that influence the damage of flood to business owners from the demographic information collected, namely “sector involved” and “year of experience”. Based on the major findings and other researchers’ suggestions, key recommendations to business owners in mitigating flood damage are also identified to reduce the adverse impact of flooding on their businesses. This study contributes better and more in-depth information on how decision-makers can assist business owners in Shah Alam in reducing the impact of future floods.